2020
DOI: 10.1080/13811118.2020.1774454
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk and Protective Factors: A Network Approach

Abstract: Method: Using an online survey, cross-sectional data was collected from a sample of 515 individuals who lived in New Zealand, Australia, the United Kingdom, and the United States of America. Participants were recruited through either social media or Prolific Academic. A network of 18 risk and protective factors for suicide was estimated using network analysis. Analyses were preregistered on the Open Science Framework.Results: Factors that had the highest strength centrality were feeling depressed, feeling hope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 80 publications
3
22
0
1
Order By: Relevance
“…In the current network, 48% of the variance of “suicide ideation” can be explained by adjacent nodes. The nodes directly and strongly linked to “suicide ideation” are depression symptoms “sadness” and “failure” and abuse event “unimportant.” The depressive symptoms directly associated with suicidal ideation are similar to those reported by previous studies ( 70 ), whereas the direct association between abuse event “unimportant” and suicidal ideation has not been explored previously. Previous studies show that neglect in early life can increase depression and anxiety symptoms and has a significant indirect effect on suicidal ideation ( 71 , 72 ), and our results extend the finding by showing that certain types of neglect can also affect suicidal ideation directly.…”
Section: Discussionsupporting
confidence: 82%
“…In the current network, 48% of the variance of “suicide ideation” can be explained by adjacent nodes. The nodes directly and strongly linked to “suicide ideation” are depression symptoms “sadness” and “failure” and abuse event “unimportant.” The depressive symptoms directly associated with suicidal ideation are similar to those reported by previous studies ( 70 ), whereas the direct association between abuse event “unimportant” and suicidal ideation has not been explored previously. Previous studies show that neglect in early life can increase depression and anxiety symptoms and has a significant indirect effect on suicidal ideation ( 71 , 72 ), and our results extend the finding by showing that certain types of neglect can also affect suicidal ideation directly.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, we found significant correlations between CHRT‐SR 7 total score or subscale scores and the WSAS, 8 a measure of psychosocial impairment that has been shown to be correlated with severity of depression and a wide range of other psychiatric symptoms and to improve when psychiatric symptoms abate 15,16 . Furthermore, participants with higher CHRT‐SR 7 scores reported lower resilience as measured by the CD‐RISC‐10, a finding that is consistent with studies using other suicide‐related measures 17,18 …”
Section: Discussionsupporting
confidence: 82%
“…15,16 Furthermore, participants with higher CHRT-SR 7 scores reported lower resilience as measured by the CD-RISC-10, a finding that is consistent with studies using other suicide-related measures. 17,18 An extensive literature has described negative help-seeking attitudes (eg, lack of perceived need), low mental health literacy (eg, treatment won't work), mental health stigma (being treated for a mental disorder will result in negative social consequences), and practical barriers (eg, lack of time or financial resources) as barriers to seeking mental health treatment. 19 Past research found that wishing to handle the problem on one's own was the most commonly reported barrier to seeking mental health care among individuals with a diagnosis of a mental disorder.…”
Section: Psychometric Properties Of the Chrt-srmentioning
confidence: 99%
“…For example, a recent study by Beurs et al [58], using a sample of 3508 young Scottish adults and a battery of psychological tests, found that: (a) internal entrapment was the factor that most contributed to current suicidal ideation, and (b) perceived burden and entrapment were statistically associated with current suicidal ideation, while depressive symptoms were associated with a history of suicidal ideation. Another study with adults [59] found that the highest strength centrality were feelings of depression, hopelessness, perceived burdensomeness, self-esteem, and social support. In particular, self-esteem and social support were shown to be central protective factors.…”
Section: Discussionmentioning
confidence: 99%